Prevalence of discordant immunologic and virologic responses in patients with AIDS under antiretroviral therapy in a specialized care center in Brazil - Casotti, Janaina Aparecida Schineider; Passos, Luciana Neves; Oliveira, Fabiano José Pereira de; Cerutti Jr, Crispim (Revista do Instituto de Medicina Tropical de São Paulo, 2011)
Some patients under antiretroviral therapy (ART) do not reach immune recovery when the viral load becomes undetectable. This is called discordant immunologic and virologic responses. Its prevalence varies between 8% and 24%. This study describes its prevalence and the characteristics of the affected subjects in the outpatient clinic of a Brazilian specialized-care center. Of 934 patients on ART, 536 had undetectable viral loads. Prevalence was 51/536 or 9% (95% confidence interval: 6.6% to 11.4%). Median age at the beginning of ART was 37 years (interquartile range - IQR: 31 to 45). Male gender and mixed race predominated (76.5% and 47.1% respectively). AIDS-defining illnesses were absent at the beginning of ART in 60.8%. Fifty-one percent were taking protease inhibitors, 43.2% Efavirenz and 5.8% both. Median time on ART was 36 months (IQR: 17-81 months). Irregular treatment was recorded for 21.6%. ART had been modified for 63% prior to the study, and 15.7% had used monotherapy or double therapy. Median CD4 count was 255 cells/mm³ (IQR: 200-284). Median viral load before ART was 4.7 log10 copies/mL (IQR: 4.5-5.2). Discordant responders were not different from AIDS patients in general, but there was a high frequency of multiple schedules of treatment.